2011
DOI: 10.1590/s1677-04202011000400007
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between photochemical efficiency (JIP-Test Parameters) and portable chlorophyll meter readings in papaya plants

Abstract: The Portable Chlorophyll Meter (PCM) is used to estimate the total chlorophyll and leaf nitrogen content of various species. Since there is a relationship between the chlorophyll concentration and the photochemical efficiency, a relationship can also be established between the PCM readings and some fluorescence variables to provide information on photosystem II (PSII) structure and activity. Papaya (Carica papaya L.) plants ['Sunrise Solo' (leaves with intense green coloring) and 'Golden' cultivars (leaves wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
2
13
0
2
Order By: Relevance
“…The decrease in chlorophyll content is combined with the TR 0 /RC decline, which was confirmed by the report of Castro et al (2011). At stages I and II of development, the differences in TR 0 /RC and ET 0 /RC values between the leaves growing under L-R/FR and H-R/FR were statistically insignificant.…”
Section: Table 2 the Values Of Chlorophyll A Fluorescence Parameterssupporting
confidence: 79%
“…The decrease in chlorophyll content is combined with the TR 0 /RC decline, which was confirmed by the report of Castro et al (2011). At stages I and II of development, the differences in TR 0 /RC and ET 0 /RC values between the leaves growing under L-R/FR and H-R/FR were statistically insignificant.…”
Section: Table 2 the Values Of Chlorophyll A Fluorescence Parameterssupporting
confidence: 79%
“…This is caused by the lower efficiency of energy transfer in plants growing under conditions simulating high insolation. The relationships between the flow parameters in this study are consistent with those obtained by Castro et al (2011) and correspond to the assumptions proposed by Strasser et al (2000).…”
Section: Photosynthetic Efficiency Of Leavessupporting
confidence: 90%
“…In the present study, a limiting factor in seedling growth was nitrogen deficiency, as indicated by the decrease in chlorophyll levels from 51 to 62 DAS, it was observed in all the treatments except 'Tainung 01' at 9.0 kPa STI. Castro et al (2011) reported that values under 20 SPAD units indicate senescence in papaya seedlings.…”
Section: Resultsmentioning
confidence: 99%